PRAKTIK SUBROGASI PERSPETIF HUKUM POSITIF DAN FATWA DEWAN SYARIAH NAIONAL (DSN-MUI) - Yunus, Muhammad; Raharto, Eko (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2022)
Subrogation is a product that exists in financial institutions as a guarantee of the debtor's debt to the creditor. Subrogation is done by transferring the old creditor's receivables to the new creditor. This study aims to determine the practice of subrogation at PT Bali Regional Development Bank Negara Branch. As well as knowing the perspective of positive law and the Fatwa of the Naional Sayariah Council (DSN-MUI) on the practice of subrogation. The method of approach used by the author is normative juridical method. The results of the study state that the practice of subrogation at PT Bank Rakyat Indonesia Kabanjahe Branch is in accordance with positive law or based on the Fatwa of the national shariah council (DSN-MUI). The transfer of credit tied to mortgage rights at Bank Rakyat Indonesia Kabanjahe Branch is in accordance with the subrogation provisions of Article 1400 of the Civil Code, especially Article 1401 sub 2 of the Civil Code. This is because the transfer of credit tied to mortgage rights at Bank Rakyat Indonesia Kabanjahe Branch fulfills the elements of subrogation even though it is not perfect. Translated with www.DeepL.com/Translator (free version)